Moral communication in elite sport - forms, functions and effects - Borggrefe, C.; Cachay, K. (Sport in Society: Cultures, Commerce, Media, Politics, 2016)
This contribution examines the use of morality in the communication between coaches and athletes in elite sport. Here, moral communication is constructed as a social fact from a systems theory perspective in order, under the light of this construction, to analyse concrete examples of it from the sports of team handball and field hockey and to reflect on its functions and effects. The findings of the analysis are incorporated in recommendations for coaches which advise a cautious use of morality since careful consideration must be given to the polemogenic nature of moral and moralizing communication.